Optimal Power Flow Scheduling Strategy for Multi-Microgrids with Multi-Time Scale Method (Journal of Solar Energy Research Updates, 2022)
Abstract: The energy management of a multi-microgrid (MG) system is essential for its stable and economic operation. This study proposes an optimal power flow scheduling strategy for the energy management of multi-MG systems. At the multi-MG level, the global central controller (GCC) is responsible for managing the MGs. The GCC calculates the amount of power exchanged within the MGs by using a novel optimal energy allocation policy. Based on the energy supply and demand mismatch, MGs are classified as providers and consumers. The GCC collects information, then distributes energy among the consumers and divides benefits to the providers. Each consumer determines the price of the purchased energy from other microgrids based on a priority parameter, in which the local load demand and renewable energy penetration rate are considered as important factors. At the MG level, with the goal of minimising the operating cost of the MG, the energy is controlled from two time scales, namely day-ahead and intraday, to optimise the output power of generators and energy storage devices. Finally, a simulation of a multi-MG system with three MGs demonstrate the effectiveness of the proposed optimal method.